Incidence of the muscular stretching as mechanical factor in the hit of pinareños boxers - Razel Martínez-Quetglas; Zelma Quetglas-González; Omar Iglesias-Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
This work was carried out with the objective of valuing the muscular visco-elastic component in the explosive stretching in the superior extremities of Pinar del Rio team boxers, in the special preparation stage of the 2012 preparatory cycle. To achieve this purpose, the Test was applied to evaluate the elastic and reactive capacities in the superior extremities, concerning the evaluation of the elastic capacity, obtaining in this measurement the numeric value that characterizes the contribution of the visco-elastic component in the explosive stretching of the superior extremities. Starting from the results of the measurement, it is evaluated the contribution of this component in the hit, comparing the results of an athlete with the others of his group, analyzing how far it is of the best result. Finally it was valued with the trainer this more precise information about the visco-elastic component contribution in the action of hitting, proposing him a group of recommendations that will allow the trainer the regulation of the training toward this component improvement to elevate the levels of production of force plosive.